Political Communication of the Ummat Party in the 2024 Election - Fuat, Atok Iful; Purwasito, Andrik; Sudarmo, Sudarmo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze how identity-based political parties develop and introduce their existence in the 2024 elections in Indonesia, focusing on the case study of the Ummat Party. Through a descriptive qualitative approach, this study explores campaign strategies and patterns of political communication used by the Ummat Party to attract voter support. The research employs a qualitative approach, focusing on the general principles underlying the manifestation of meaning from social phenomena in society. Findings indicate that identity politics, particularly based on ethnicity and religion, dominate the campaign strategies of political parties, albeit controversially. While successful in garnering voter support, identity politics also generates social and political impacts that require further attention. Implications of identity politics on the political system and national unity are of primary concern, demanding in-depth analysis of the political and social dynamics in Indonesia. This study provides valuable insights into the role of identity politics in the Indonesian electoral context and lays the groundwork for further research on this topic.